Rethinking pre-training: cognitive load implications for learners with varying prior knowledge - Gorbunova, Anna; Kapuza, Anastasiia; Chen, Ouhao; Costley, Jamie (Frontiers in Psychology, 2025)
This study examines how prior knowledge and pre-training relate to cognitive load during problem-solving. Grounded in cognitive load theory, it investigates whether pre-training facilitates learning by reducing cognitive load or imposes redundant information for learners with higher prior knowledge. In an experiment with 136 university students, pre-training was implemented through concept maps and a glossary introducing essential terms and procedures before problem-solving. Results revealed that learners with higher prior knowledge experienced lower intrinsic and extraneous load and higher germane load during problem-solving compared to learners with lower prior knowledge, suggesting enhanced schema refinement rather than redundancy. Pre-training consistently reduced extraneous load across all learners, including those with higher prior knowledge, challenging the expected expertise reversal effect. While learners with lower prior knowledge did not show significant reductions in intrinsic load, they benefited from decreased extraneous load during problem-solving. These findings highlight the value of pre-training as an instructional strategy and underscore the importance of aligning instructional design with learners’ existing knowledge.